In sılıco ANALYSIS OF NOVEL ANTICANCER AGENTS AS BRD4 INHIBITORS (Applied Biological Research, 2023)
The BET BRD4 proteins, involved in cancer, are of prime importance in  developing anticancer drugs. Cancer is marked by the uncontrolled growtof abnormal cells anywhere in the body with the potential to spread or  invade other body parts. The core nature of disease lies in defying normal  cell signals, be it anti-growth signals, death signals or apoptosis, and tissue  invasion metastasis. In present work, we have designed and tested novel  quinazolinone-based derivatives to establish them as a better anticancer  agent against the BRD4 target. The selection of BRD4 protein in this work  is based on earlier findings that reported the role of BRD4 in various  cancers such as lymphoma, multiple myeloma, acute myeloid leukemia,  acute lymphoblastic leukemia, chronic myeloid leukemia, solid tumours,  prostate cancer, nervous system tumour, colorectal cancer, and breast  cancer. Molecular docking was performed by using Glide docking module  of the Schrodinger suite. The XP Glide docking studies, ADME  (absorption, distribution, metabolism, excretion) profile test, binding  energy calculations, and drug-likeness was performed to get the best BRD4  inhibitor ligand. Out of 16 quinazolinone derivates, ten ligands had better  XP Glide score, 4 were marginally less, and 2 gave poor score than the  standard drug LY2 (-6.779 kcal mol-1). The best ligand had a score of -9.866  kcal mol-1 which was 45% more efficient than LY2, so appears to be more  effective and potent anticancer inhibitor ligands for BRD4 protein.
Keywords: Anticancer drugs; BET BRD4 proteins; molecular docking; protein inhibition; quinazolinone derivatives; targeted therapy